PENGARUH DURASI DAN CONVEXITY TERHADAP HARGA OBLIGASI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Silalahi, Donalson; Laoly, Eka Putri (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to determine and explain the effect of duration and convexity on bond prices in banking companies listed on the Indonesia Stock Exchange for the 2017-2021 period. To achieve this aim, research was carried out using purposive sampling techniques, thus obtaining a sample of 11 banking companies that issued bonds with a research period of five years. The analysis model used is a multiple linear regression model. The research results show that: First, duration has a positive and significant effect on bond prices, convexity has a positive and insignificant effect on bond prices. The ability of duration and convexity to explain variations in bond prices is 2.9 percent. Second, duration has a positive and significant effect on bond prices, convexity has a negative and significant effect on bond prices in the discount price group. Duration has a positive and significant effect on bond prices, convexity has a positive and significant effect on bond prices in the premium price group. The ability of duration and convexity to explain variations in bond prices is in the range of 92.8-94.4 percent.